EVALUATION OF LEAD, CADMIUM AND MERCURY CONTENT IN SPORTS SUPPLEMENTS IN THE MARKET OF IRAN: Pharmaceutical Science-Analysis - MEHRAN SEPEHRARA; NOSHIN ADIB; PEDRAM EBRAHIMNEJAD (International Journal of Life Science and Pharma Research, 2022)
This study was aimed to determine the Lead, Cadmium and Mercury content in the Sports supplements in the market of Iran. This cross-sectional study was to determine the Lead, Cadmium and Mercury level in the 12 available Sports supplements brands in Iran. The total of 60 samples was used for this purpose. HNO3 67% and HF40% were used to extract the metals. The heavy metal levels in samples were determined using atomic absorption spectrometry method. The obtained results were finally analyzed by ANOVA and descriptive statistics using software spss16.The results showed that highest level of lead was detected in brands of S12 (2.31±0.01) and S11 (1.95± 0.003) while the lowest average level was detected in S1 brand (0.003± 0.0007). The highest level of Cadmium was in brands of S9 (0.412±0.007) and S11 (0.704± 0.003) and lowest average level of Cadmium was detected in S5 brand (0.012± 0.002). The maximum level of mercury was determined in S8 brand (0.55± 0.025) and S9 brand (0.50± 0.020) while the minimum level was observed in S1 brand (0.11± 0.011). It can be concluded that there are various amount of heavy metals in the sports supplements in the Iran and the monitoring of these products is important to protect the athletes’ health.